Physicochemical control of bacterial and protist community composition and diversity in Antarctic sea ice. (7th May 2015) - Torstensson, Anders; Dinasquet, Julie; Chierici, Melissa; Fransson, Agneta; Riemann, Lasse; Wulff, Angela
Summary: Due to climate change, sea ice experiences changes in terms of extent and physical properties. In order to understand how sea ice microbial communities are affected by changes in physicochemical properties of the ice, we used 454‐sequencing of 16S and 18S rRNA genes to examine environmental control of microbial diversity and composition in Antarctic sea ice. We observed a high diversity and richness of bacteria, which were strongly negatively correlated with temperature and positively with brine salinity. We suggest that bacterial diversity in sea ice is mainly controlled by physicochemical properties of the ice, such as temperature and salinity, and that sea ice bacterial communities are sensitive to seasonal and environmental changes. For the first time in Antarctic interior sea ice, we observed a strong eukaryotic dominance of the dinoflagellate phylotype SL163A10, comprising 63% of the total sequences. This phylotype is known to be kleptoplastic and could be a significant primary producer in sea ice. We conclude that mixotrophic flagellates may play a greater role in the sea ice microbial ecosystem than previously believed, and not only during the polar night but also during summer when potential food sources are abundant.